Effect of graphene oxide loading on TiO2: Morphological, optical, interfacial charge dynamics-A combined experimental and theoretical study. (March 2019) - Yadav, A.; Yadav, M.; Gupta, S.; Popat, Y.; Gangan, A.; Chakraborty, B.; Ramaniah, L.M.; Fernandes, R.; Miotello, A.; Press, M.R.; Patel, N.
Abstract: Reduced graphene oxide (rGO)TiO2 composites are prepared using photo-reduction method by varying GO to TiO2 weight ratio from low (rGOT-0.001, 0.01, & 0.1) to high (rGOT-1, 3 & 10) range and its effect on morphological, optical and mechanism of fast charge dynamics at the interface are investigated. Experimental analysis confirm that reduction process improves as TiO2 amount increases in rGO-TiO2 but leads to aggregation of TiO2 nanoparticles. rGOT-3 composite displayed the highest photocatalytic activity for degradation of phenols compared to TiO2, GO and other composites. This was achieved due to uniform dispersion of TiO2 nanoparticles over rGO surface, which enables distinct formation of TiOC bond between each TiO2 nanoparticle and rGO surface, and results in slight red shift in the band edge. This TiOC bond facilitates fast electron transfer from TiO2 to rGO and reduces recombination rate as revealed by photoluminescence and time resolved photoluminescence spectroscopy. The experimental findings were further investigated using density functional theory simulations. Band structure calculation confirms high mobility states induced within the band gap due to formation of TiOC bond in rGO-TiO2 model which assists in fast electron transfer from TiO2 to rGO during the photocatalytic process and hence reduces recombination rate. Graphical abstract: